Potential for co-metabolic oxidation of TCE and evidence for its occurrence in a large-scale aquifer survey. (15th March 2020) - Gafni, Almog; Siebner, Hagar; Bernstein, Anat
Abstract: Trichloroethylene (TCE) is a groundwater pollutant that is prevalent worldwide. In contaminated groundwater, TCE can be biodegraded following either reductive dechlorination or aerobic co-metabolic oxidation. However, since the co-metabolic process is not accompanied by indicative and easily detectable transformation products, little is known about its prominence in the environment. To estimate the environmental importance of the oxidative process, a regional groundwater survey was conducted. In this survey, polluted water from 100 wells along the Israeli Coastal Aquifer was sampled. Geochemical data indicated oxic conditions prevailing in most sites. The sampled groundwater was used for microcosm experiments, functional gene analysis, and TCE compound-specific isotope analysis (δ 13 C and δ 37 Cl). Enrichments of methane and toluene oxidizers in microcosms indicated the high potential of the indigenous microbial community to co-metabolically oxidize TCE. This was further reinforced by the high abundance of mmoX and PHE functional genes quantified in some of the sites (yet lower abundance of TOD functional gene was found). Finally, compound-specific isotope analysis was used to assess the magnitude of TCE oxidation in practice. Applying the isotopic tool for scattered points on a regional scale demanded the consideration of a wide δ 13 C range of source TCE, hampering the ability to detect small shifts of a single permil. Thus, despite the high potential for the oxidation process, no evidence was attained for the natural occurrence of the process, and significant isotopic shifts were restricted to actively treated sites only. This limitation should be considered in future regional scale studies, in which no single source is defined. Graphical abstract: Image 1 Highlights: The importance of TCE co-metabolic oxidation in groundwater is unknown. This was assesses by microcosms, functional genes analysis, and CSIA. A total of 100 polluted wells of unknown sources were sampled along a regional aquifer. Potential for TCE co-metabolic oxidation was found to be widespread in the aquifer. The actual occurrence of the process, as determined by CSIA, remains questioned.